INTRAVITREAL BEVACIZUMAB ALONE VERSUS INTRAVITREAL BEVACIZUMAB IN COMBINATION WITH FOCAL MACULAR PHOTOCOAGULATION IN DIABETIC MACULAR OEDEMA - Jatoi, Asadullah; Shaikh, Noman Ahmed; Narsani, Ashok Kumar; Asma Jatoi (Journal of Ayub Medical College Abbottabad, 2022)
Background: To compare the mean best corrected visual acuity (BCVA) between intravitreal bevacizumab (IVB) and combination treatment bevacizumab and Focal Macular Photocoagulation (FMP) for diabetic macular oedema (DME). Method: It is a randomized control trial conducted at Department of ophthalmology at Institute of Ophthalmology, Liaquat University of medical and health sciences, Jamshoro from 1st November 2019 to 31st October 2020, in which 260 Patients between the ages of 40 to 75 years, with DME were included. While patients with macular oedema secondary to other causes than diabetic retinopathy, presence of vitreomacular traction, aphakic patients, history of glaucoma or who had received pan-retinal photocoagulation, IVB, triamcinolone within 12 months, patients with history of stroke or cardiac disease, patients with media opacities such as corneal opacities were also excluded from the study. Two hundred sixty (260) patients were divided in two groups. Group A has 130 patients and they were treated with IVB alone. Group B also included 130, and they were treated with combination of IVB+FMP. The patients were followed-up monthly for 3 months and BCVA was checked at the end of 3 months. Results: Patients in group B showed superior visual outcome, when they were treated with IVB+FMC as compared to patients in group A who received IVB alone. Conclusion: Combination treatment OF IVB+FMP is an effective treatment option for diabetic macular oedema as compared to IVB alone with better mean visual outcome.